Structural characterization of fructans from Agave fourcroydes (Lem.) with potential as prebiotic - García-Curbelo, Yanelys; López, Mercedes G.; Bocourt, R.; Collado, Erika; Albelo, Nereyda; Nuñez, Odalys (Cuban Journal of Agricultural Science, 2016)
The use of prebiotics, like fructans, increases in animal production. They can be used as growth promoting additives because they benefit health and productive performance. Agave fourcroydes shows high concentrations of these compounds. Besides, structural characteristics of these carbohydrates may influence on animal response. The objective of this study was to determine structural characteristics of fructans present in Agave fourcroydes from Cuba, with potential as prebiotic in animal feeding. An amount of 10 stems of Agave fourcroydes were used, which belonged to the Empresa Henequenera “Eladio Hernández León”, located in Matanzas province, Cuba. For structural characterization, thin layer chromatography, gas chromatography coupled to a mass spectrometry and anion- exchange chromatography of high resolution coupled to an amperometric detector were used. From the obtained results, a complex mixture of oligosaccharides, which present few ramifications and neo-kestose series, insulin (GFn) and inulo-nose (Fn), is proposed as structure for fructans of Agave fourcroydes. Structural characteristics of these carbohydrates are essential for animal nutrition. Fructans of Agave fourcroydes are considered as prebiotic candidate for being natural sources of oligofructans, estimated as the best substrates for acid-lactic bacteria.Keywords: chemical stuctures, Agave fourcroydes, fructan, prebiotic